PEMIKIRAN IMAM AL-GHAZALI DALAM KEPEMIMPINAN PENDIDIKAN - Zulkarnaen Guchi, M. Padhil, Ramlan Padang, (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2022)
The purpose of this study is to know the concept of Imam Al-Ghazali regarding educational leadership, to know the concept of Imam Al-Ghazali regarding the characteristics of educational leadership. know Imam Al-Ghazali's concept regarding educational methods and know Imam Al-Ghazali's concept regarding educational goals. In this study, the authors used a descriptive research method of literature, namely trying to examine and analyze the object of study using reference literature, both primary and secondary. After that, the researcher carried out categorization and analysis. The results of the study concluded as follows: 1) The division of knowledge of educational leadership according to Imam according to Imam al-Ghazali there are two, namely a) muamalah science includes the science of fardu ain. The science of fardu ain is a science that must be learned including the science of monotheism, divinity, and others. While fardu kifayah science is divided into three parts; commendable knowledge (sharia and general), knowledge that is obligatory, and knowledge that is despicable. b) Mukasyafah science, namely knowledge obtained through inspiration, 2) The concept of educational leadership according to Imam al-Ghazali includes: a) Imam al-Ghazali's views on students and educational goals, b) Imam al-Ghazali's views on teachers and children's education, c ) Views of Imam al-Ghazali regarding the Goals of Knowledge, d) Views of Imam al-Ghazali regarding the classification of the importance of knowledge: First, the Qur'an, religious sciences, fiqh sunnah and interpretation. The second is the sciences of language, nahwu science, tajwid. Third, knowledge that is included in the obligatory kifayah category, namely medicine, arithmetic, skills including political science. Fourth, namely cultural sciences such as poetry, history, philosophy, mathematics, logic.